1999
DOI: 10.1177/00220345990780041101
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Durability of Dentin Bonds Made with a Self-etching Primer, in vivo

Abstract: The long-term durability of bonds between adhesive resins and dentin is of significant importance for the longevity of bonded restorations. We carried out an in vivo one-year study to evaluate the durability of resin-dentin bonds in the oral cavity, as well as to test the hypothesis that the adhesive interface would show morphological changes in vivo over time. Very shallow saucer-shaped dentin cavities were prepared in 12 intact teeth of one Japanese monkey (Macaca fuscata) under general anesthesia. The cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
320
1
76

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(406 citation statements)
references
References 12 publications
9
320
1
76
Order By: Relevance
“…However, marginal discoloration or recurrent caries are frequently found in clinical resin restoration for long-term use. Several in vivo [1][2][3][4] and in vitro studies [5][6][7][8] have shown the degradation mechanism of the bonds. However, information on bond degradation is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, marginal discoloration or recurrent caries are frequently found in clinical resin restoration for long-term use. Several in vivo [1][2][3][4] and in vitro studies [5][6][7][8] have shown the degradation mechanism of the bonds. However, information on bond degradation is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Neste sentido, o presente estudo foi desenvolvido a fim de analisar o efeito da radiação ionizante na na resistência adesiva entre dentina e resina. Trata-se de uma avaliação de curto prazo, já que as restaurações foram confeccionadas logo após a irradiação dos dentes, e a análise através da resistência de união foi utilizada por ser considerada uma propriedade de fundamental importância para a possível durabilidade das restaurações (24,25).…”
Section: Discussionunclassified
“…Achieving a strong and durable bond between adhesive resins and dental substrates is of critical importance for the longevity of bonded restorations 1) . The introduction of dentin primers has remarkably improved the efficacy of dentin bonding systems 2) .…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of dentin primers has remarkably improved the efficacy of dentin bonding systems 2) . Self-etching primer systems combine the etching and priming steps into one agent 1) , while all-in-one systems combine the self-etching primer and bonding agent into one application step 3) . Most of the current adhesive materials are capable of achieving high bond strength values shortly after polymerization 4,5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation